2015
DOI: 10.4155/tde.15.79
|View full text |Cite
|
Sign up to set email alerts
|

Transport of digoxin-loaded Polymeric Nanoparticles Across BeWo cells, an In Vitro Model of Human Placental Trophoblast

Abstract: Background: Fetal arrhythmias can lead to fetal congestive heart failure and hydrops fetalis. Digoxin (the first-line treatment) has low transplacental permeability and high risk of maternal side effects. Biodegradable digoxin-loaded PEGylated poly(lactic-co-glycolic acid) nanoparticles may increase digoxin transport across BeWo b30 cell monolayers (an in vitro model of trophoblast in human placenta) by reducing the drug's interaction with P-gp. Results/methodology: The nanoparticles showed high encapsulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…TEER values between 30 and 60 Ω⋅cm 2 were considered acceptable for performing transport studies. 12 Moreover, antibody staining for the tight junction protein ZO-1 was performed on day 6 PS to examine barrier integrity in the confluent cell monolayer. DAPI counterstaining was used to visualize the nuclei.…”
Section: Monolayer Confirmationmentioning
confidence: 99%
See 1 more Smart Citation
“…TEER values between 30 and 60 Ω⋅cm 2 were considered acceptable for performing transport studies. 12 Moreover, antibody staining for the tight junction protein ZO-1 was performed on day 6 PS to examine barrier integrity in the confluent cell monolayer. DAPI counterstaining was used to visualize the nuclei.…”
Section: Monolayer Confirmationmentioning
confidence: 99%
“…This study provided a novel approach to the treatment of fetal diseases such as cardiac arrhythmia. 12 Grafmueller et al 13 analyzed the bidirectional transfer of plain and carboxylatemodified polystyrene particles ranging in size between 50 and 300 nm using the ex vivo human placental perfusion model. This study indicated that the main translocation mechanism is likely to involve an active, energy-dependent transport pathway.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that certain types of nanoparticles are capable of crossing the placental barrier, or causing indirect effects to placental or fetal development [53,100102]. Endocytosis of nanoparticles by the placenta is important in that it can alter the transplacental passage of drugs.…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
“…Endocytosis of nanoparticles by the placenta is important in that it can alter the transplacental passage of drugs. An example of this is the passage of nanoparticles made of the polymer poly(lactic- co -glycolic acid) (PLGA) or its PEGylated block copolymer, which may alter or prevent drug binding to efflux transporters and potentially alter their metabolism [102,103]. Other nanoparticles, such as poly(amidoamine) dendrimers and silica nanoparticles, however, may demonstrate reduced transfer across the placenta as compared to polystyrene or PLGA nanoparticles [100,101,103,104].…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
“…The BeWo cell line has been shown to be a useful in vitro placental barrier model for studying adhesion, transport, and infection [11], with many researchers using BeWo cells as an in vitro barrier model of the placenta to explore the transport and toxicity of foreign agents or organisms [12,13].…”
Section: Introductionmentioning
confidence: 99%